2019
DOI: 10.1055/a-1014-2809
|View full text |Cite
|
Sign up to set email alerts
|

Half Soccer Season Induced Physical Conditioning Adaptations in Elite Youth Players

Abstract: This study aimed to investigate training-induced fitness changes and their relationship with training-competition load during half a soccer season (18 wks). Training load [heart rate (HR) and ratings of perceived exertion (RPE)] and match time were monitored, including 108 training (3 223 individuals) and 23 match sessions, in 38 youth elite male soccer players. Fitness variables were assessed before and after the study. Yo-Yo intermittent recovery test 1 (Yo-Yo IRT1) improved (P<0.001; 90%CI: 418–632 m; ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
3
0
3
Order By: Relevance
“…To our knowledge, this is the first study showing the evolution of physical performance throughout an entire season in female football players. Most of the studies carried out so far are based on punctual determinations at one moment throughout a season [ 19 , 22 , 27 ]. Our study comprises a whole season of a total of 27 players from two teams playing in the same football category.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study showing the evolution of physical performance throughout an entire season in female football players. Most of the studies carried out so far are based on punctual determinations at one moment throughout a season [ 19 , 22 , 27 ]. Our study comprises a whole season of a total of 27 players from two teams playing in the same football category.…”
Section: Discussionmentioning
confidence: 99%
“…Hay divergencias en la progresión respecto a series y repeticiones, ya que hay investigaciones que plantean un incremento dentro del mismo protocolo tanto de las series, como de las repeticiones (Gavanda et al, 2019), y otros los mantienen durante la intervención (Asadi et al, 2018). Desde el punto de vista de los principios del entrenamiento sería conveniente realizar una progresión de la carga para seguir consiguiendo adaptaciones (Asadi et al, 2018;Pena-González et al, 2019), aunque al ser las intervenciones planteadas en estos estudios cortas en el tiempo, es posible que no se haya llegado al estancamiento que provocaría la no progresión en este sentido (Arregui-Martin et al, 2020;Sánchez-Sánchez, Pérez, Yagüe, intensidad explosiva, y una velocidad elevada a la hora de realizar los ejercicios pliométricos (Asadi et al, 2018;Beato et al, 2018;Lloyd, Oliver, Myer, De Ste Croix, & Read, 2020;Loturco et al, 2020;McKinlay et al, 2018;Ramirez-Campillo et al, 2019).…”
Section: Discussionunclassified
“…El fútbol es un deporte colectivo de carácter predominantemente aeróbico, en el que destacan las acciones de naturaleza intermitente, caracterizadas por un predominio del metabolismo anaeróbico y la capacidad de aplicar fuerza (Arregui-Martin, Garcia-Tabar, & Gorostiaga, 2020;Pena-González, Fernández-Fernández, Cervelló, & Moya-Ramón, 2019;. No en vano, la capacidad de los futbolistas de generar fuerza, y la eficiencia del sistema muscular y de los patrones de movimiento, son los factores que más afectan al rendimiento en acciones muy frecuentes en el fútbol como pueden ser los sprints, cambios de dirección o saltos (Arregui-Martin et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Soccer is an acyclic sport, in which low to moderate intensity actions are interchanged with repeated explosive actions during the game [1]. It has been reported that the external load is influenced by the age of the players; thus, soccer players under 15 years of age (U-15) cover approximately 6 to 8 km and perform ~80 accelerations (>1 m•s −2 ) per match with a duration of 2 and 4 s each [2].…”
Section: Introductionmentioning
confidence: 99%